Pemanfaatan Ranting Pruning Jati dan Serasah Daun Area Reklamasi PT Semen Indonesia (Persero) Tbk Pabrik Tuban Sebagai Bahan Bakar Alternatif Berkelanjutan - Setyo Budi, Agus; Hajar Hantoro, Arthur; Tarigan, Agrifa; Hermawanto, Moch. Khalik (Jurnal Serambi Engineering, 2025)
The cement industry is one of the sectors with high energy intensity and a significant contributor to greenhouse gas emissions. This study aims to evaluate the utilization of biomass waste in the form of teak pruning twigs and leaf litter from the post-mining reclamation area of PT Semen Indonesia (Persero) Tbk Tuban Plant as a sustainable alternative fuel. The methods used include the collection, natural drying, and shredding of biomass to a size of less than 2 cm, which is then used as a partial substitute for coal in the kiln combustion process. The results show that this innovation successfully reduced heat energy consumption by 1008 GJ, saved operational costs of IDR 32,800,913, and reduced carbon emissions by approximately CO2 96.728 tons of CO2 from January 2024 to June 2025. This program not only improved energy efficiency and environmental performance but also transformed the value chain into a more collaborative and sustainable one, supporting the principles of the circular economy.